Biosynthesis and properties of the adenovirus 2 L1-encoded 52,000- and 55,000-Mr proteins. - Lucher, L A (1986)
The adenovirus type 2 L1 region, which is located at 30.7 to 39.2 map units on the viral genome, is transcribed from the major late promoter during both early and late stages of virus replication, and a 52,000-Mr (52K) protein-55K protein doublet has been translated in vitro on L1-specific RNA. To investigate the biosynthesis and properties of the L1 52K and 55K proteins, we prepared antibody against a synthetic peptide encoded near the predicted N terminus. As determined by immunoprecipitation and immunoblot analysis, the antipeptide antibody recognized major 52K and 55K proteins synthesized in adenovirus type 2-infected cells that appeared to be identical to the 52K-55K doublet translated in vitro. The immunoprecipitated 52K and 55K proteins were very closely related, as shown by a peptide map analysis. Both L1 proteins were phosphorylated, and they were phosphorylated at similar sites. No precursor-product relationship was detected between the 52K and 55K proteins by a pulse-chase analysis. Biosynthesis of the L1 52K and 55K proteins began about 6 to 7 h postinfection, after biosynthesis of the early region 1A and early region 1B 19K (175R) T antigens, and reached a maximum rate at about 15 h; the maximum rate was maintained until at least 25 h postinfection. At all times, the 55K protein appeared to be synthesized at a severalfold-higher level than the 52K protein. Both proteins were quite stable and accumulated until late times after infection. Viral DNA replication was not essential for formation of the L1 proteins. Thus, the L1 52K-55K gene appears to be regulated in a manner different from the classical early and late viral genes but similar to the protein encoded by the i-leader (Symington et al., J. Virol. 57:849-856, 1986). The L1 proteins were detected in the cell nucleus by immunofluorescence microscopy with antipeptide antibody and were found to be primarily associated with the nuclear membrane by an immunoblot analysis of subcellular fractions.